2020
DOI: 10.21660/2020.73.96594
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Effects of Rectangular Embankment Loading Placed on Soft Ground

Abstract: Although geotechnical problems are inherently three-dimensional (3D), they are frequently approximated by one-dimensional (1D) or two-dimensional (2D) analyses. These simplifications are often based on certain assumptions. However, the use of simplified analyses under conditions where the 3D effects cannot be ignored reduces the accuracy of future predictions. This study aimed to investigate the relevance of plane strain analyses and 3D analyses, considering the 3D effects on typical load problems. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…The important aspect of this method is that it considers the correlation between the plane strain analysis results and the three-dimensional analysis results. This technique applies a method that the authors confirmed to be applicable to the deformation of the surrounding ground due to embankments [9].…”
Section: Introductionmentioning
confidence: 99%
“…The important aspect of this method is that it considers the correlation between the plane strain analysis results and the three-dimensional analysis results. This technique applies a method that the authors confirmed to be applicable to the deformation of the surrounding ground due to embankments [9].…”
Section: Introductionmentioning
confidence: 99%